1980
DOI: 10.1038/clpt.1980.52
|View full text |Cite
|
Sign up to set email alerts
|

Intranasal and oral cocaine kinetics

Abstract: Plasma cocaine levels were determined in 7 subjects after intranasal and oral cocaine. Intranasal doses of 0.19, 0.38, 0.75, 1.5, and 2.0 mg/kg were given as a 10% aqueous solution; 0.38 mg/kg was given as crystalline cocaine HCl. Oral cocaine was administered in doses of 2.0 and 3.0 mg/kg. Intranasal cocaine kinetics were described by a 1-compartment open model with 2 consecutive first-order input steps and first-order elimination. Oral cocaine disposition was described by a 1-compartment open model with a la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
59
2
5

Year Published

1984
1984
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 220 publications
(71 citation statements)
references
References 7 publications
3
59
2
5
Order By: Relevance
“…The drug was given orally (20 mg/kg/day in fruit or candy treats) twice a day at 7:00 A.M. and 7:00 P.M. The oral administration of cocaine models the snorting of this drug by human addicts because the pharmacokinetics of cocaine administered orally closely resemble that achieved through intranasal application (Wilkinson et al, 1980;Jatlow, 1988;Jufer et al, 1998;Fattinger et al, 2000). The timing, dose, and route of drug administration employed in this study were identical to those successfully used in our previous investigations on the effects of prenatal cocaine exposure on cerebral cortical development in primates (Lidow, 1995).…”
Section: Materials and Methods Cocaine Treatmentmentioning
confidence: 99%
“…The drug was given orally (20 mg/kg/day in fruit or candy treats) twice a day at 7:00 A.M. and 7:00 P.M. The oral administration of cocaine models the snorting of this drug by human addicts because the pharmacokinetics of cocaine administered orally closely resemble that achieved through intranasal application (Wilkinson et al, 1980;Jatlow, 1988;Jufer et al, 1998;Fattinger et al, 2000). The timing, dose, and route of drug administration employed in this study were identical to those successfully used in our previous investigations on the effects of prenatal cocaine exposure on cerebral cortical development in primates (Lidow, 1995).…”
Section: Materials and Methods Cocaine Treatmentmentioning
confidence: 99%
“…However, the AUC inf was significantly higher (p Ͻ 0.05) for AHN 2-003 (15,152 mg/l⅐h) and AHN 1-055 (10,699 mg/l⅐h) compared with cocaine. Cocaine is known to be rapidly metabolized by plasma esterases and has a significantly shorter t 1/2 as discussed below (Wilkinson et al, 1980;Mets et al, 1999). The low AUC inf for cocaine in comparison with AHN 2-003 and AHN 1-055 is most likely due to this extensive metabolism…”
Section: Downloaded Frommentioning
confidence: 99%
“…This pharmacokinetic profile would most likely allow for a gradual increase in brain dopamine levels resulting in slow inhibition of dopamine reuptake along with a sustained elevation of dopamine. Cocaine is rapidly absorbed and metabolized after administration (Wilkinson et al, 1980;Mets et al, 1999). Thus, a pharmacokinetic profile different from cocaine might also be a determining factor in predicting the therapeutic efficacy of a potential substitute agent.…”
mentioning
confidence: 99%
“…Baselt [9] demon strated that an acidic pH is superior to the addition of sodium fluoride in maintaining the stability of cocaine in plasma samples. Using other species, we have determined elimination half-life of the cocaine to be 46 min in pregnant rats [10] and 74 min in dogs [Kantor et al, submitted], similar to values reported for humans (40 min) [11], While interspecies differences in drug dispo sition are well recognized, the value of using the pregnant ewe for these studies cannot be overemphasized. For the present time, the fetal lamb continues to be a good animal model for these studies because so much is already known about its physiology and pharmacological response to a variety of drugs.…”
Section: Discussionmentioning
confidence: 94%